Upor proti italijanizaciji - Bajc, Gorazd (Studia Historica Slovenica, 2014)
The article presents a critical overview of the politics and culture of Slovenes in Trieste and in the whole territory of Venezia Giulia in the period from 1918 to 1941, which was the period of fascist assimilation. It outlines the activities of nationalist-liberal and Christian-socialist politicians and left-wing politicians, as well as the cultural and educational work in societies, educational institutions, publications, and sports. Furthermore it describes the "transfer" of culture into illegalitz at the end of 1920s. The author's purpose was, first, to present a historical overview of the presented topics mainly based on the material published in recent years, and second, to point out that there are still some questions that remain open.
Keywords: društva; fašizem; Julijska krajina; narodna zavest; Slovenci; Trst